2020
DOI: 10.1016/j.csbj.2020.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Permeation mechanisms through the selectivity filter and the open helix bundle crossing gate of GIRK2

Abstract: Graphical abstract Permeation mechanisms through the selectivity filter (SF) and helix bundle crossing (HBC) gate of GIRK2 channel. Water and K + ions co-translocate through the SF in a water-K + coupled manner from the extracellular matrix into the intracellular side with the aid of an external electric field. A tilt of the SF affects its recognition efficiency. A 4-K + occupancy in the SF-HBC cavity is required for the permeation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 60 publications
2
9
0
Order By: Relevance
“…The Root Mean Square Deviation (Equation 1) which is used to represent the difference between two structures are shown in Figure 2A, indicating that all the simulation systems went smoothly after around 600 ns. The number of permeated K + ions in the GIRK2-Na + -G system is greater than that of the other two (Figure 2B), which is consistent with the results of electrophysiological experiments 23 , suggesting the reliability of our calculation results.…”
Section: Na + and G Subunits Work Together To Activate The Girk2 Ch...supporting
confidence: 89%
See 2 more Smart Citations
“…The Root Mean Square Deviation (Equation 1) which is used to represent the difference between two structures are shown in Figure 2A, indicating that all the simulation systems went smoothly after around 600 ns. The number of permeated K + ions in the GIRK2-Na + -G system is greater than that of the other two (Figure 2B), which is consistent with the results of electrophysiological experiments 23 , suggesting the reliability of our calculation results.…”
Section: Na + and G Subunits Work Together To Activate The Girk2 Ch...supporting
confidence: 89%
“…Five K + went only across the G-loop gate (the average time of 188 ns) in GIRK2-Na + , while three ions passed through Gloop gate (the average time of 298.7 ns) and HBC in GIRK2-G. These results above have indicated that Na + and G activated the GIRK2 channel together, but inactivated the channel alone, which appears to differ from the previous conclusion that both Na + and G can activate the GIRK2 channel individually 8,23 . This may be due to the inwardly rectifying effects and the limited simulation time scale (1 s), which means that the outflow of K + in the inwardly rectifying channel is much more difficult than the inflow and longer time is thus required for the permeation events.…”
Section: Na + and G Subunits Work Together To Activate The Girk2 Ch...mentioning
confidence: 62%
See 1 more Smart Citation
“…Previous studies 5 10 , 40 42 have identified ligand-dependent conformational changes important for GIRK2 activity and suggest a complex allosteric network connecting the gates and the modulatory binding sites. Consensus exists about the relevance of large scale movements, such as rotation and rocking of the CTD and bending of transmembrane helix 2 for channel activity, while several aspects about the detailed coupling underlying channel opening have been revealed 6 – 11 .…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Chen et al 48 suggested coupling between the SF and the Gβγ-binding site of mGIRK2 based on electrophysiology experiments that revealed mGIRK2 wv stimulation by the channel activator Ivermectin, but not the Gβγ-mediated pathway. Furthermore, Li et al 42 described the GIRK2 SF as a crucial determinant for K + permeation, which can be influenced by binding of Gβγ and Na + . In line with these studies, our findings demonstrate a coupling between the GIRK2 SF and the Gβγ binding site corroborated by both experimental and computational data.…”
Section: Discussionmentioning
confidence: 99%